A high-throughput multiplex tandem PCR assay for the screening of genetically modified maize. (January 2018) - Wei, Shuang; Wang, Chenguang; Zhu, Pengyu; Zhou, Guangbiao; Fu, Wei; Wu, Xiyang
Abstract: Genetically modified organisms (GMO) are increasingly gaining acceptance, which has led to an increasing demand for high-throughput methods for their detection. This study describes development of a high-throughput and low-cost multiplex tandem PCR (MT-PCR) assay for the screening of transgenic maize of 14 targets, containing 7 genetically modified (GM) common screening elements, 6 transgenic maize events and a maize reference gene, using SYBR Green I for quantification. The 14-target high-throughput multiplex tandem PCR assay successfully amplified products from single-event samples with a GM maize DNA amount less to 0.001 ng, and displayed high specificity. This assay can efficiently be used for screening GM maize in foods and feeds. Highlights: A high-throughput screening system was developed for detection of GM maize. The system utilized multiplex tandem PCR for 14 targets detection. The method allowed for amplification of less to 0.001 ng of the template DNA. This method contributes to detecting unauthorized GMOs released into the markets.